Productivity and the poor?: political economy of village pond fishery in the Indo-Gangetic Basin - Shah, Tushaar; Indu, R. (Informa UK Limited, 2014)
India’s 2.25 million ha of village tanks were for centuries loosely managed as multiple use common property resources, including for fishing by artisanal fisher-folk, the lowest in the social hierarchy. During the 1970s and after, the aquaculture productivity revolution created a vibrant new political economy by increasing manyfold the value of fishing rights in these tanks. This productivity boom was expected to improve the lot of poor artisanal fisher communities. But has this happened? This study across the Indo-Gangetic Basin suggests increasing elite capture of these community-owned resources. Capital, technology and muscle power have determined who benefits; artisanal fishers have none of these.